Handbook of statistical bioinformatics - Lu, Henry Horng-Shing; Schölkopf, Bernhard; Zhao, Hongyu (Springer handbooks of computational statistics., 2011)
Numerous fascinating breakthroughs in biotechnology have generated large volumes and diverse types of high throughput data that demand the development of efficient and appropriate tools in computational statistics integrated with biological knowledge and computational algorithms. This volume collects contributed chapters from leading researchers to survey the many active research topics and promote the visibility of this research area. This volume is intended to provide an introductory and reference book for students and researchers who are interested in the recent developments of computational statistics in computational biology.